Comparison of efficacy between herbal capsule of anise and mefenamic acid on postpartum after-pain - G Ozgoli; A Khodadie; Z Mojab; S Jambarsang; F Sheikhan; S Taleb (Journal of Medicinal Plants, 2017)
Introduction: Postpartum after pain relief is effective in convenience of the mother and improve her interaction with the newborn.one of the ways of pain relief is using herbal medicines.